Ecological Constraints of Timescales, Production, and Perception in Temporal Experiences of Music - God, Rolf Inge (Empirical Musicology Review, 2015)
In trying to structure our discussions of temporal experience in music, it could be useful to have a look at some basic ecological constraints of timescales, production, and perception of music. This may hopefully help us to distinguish between on the one hand readily perceived features of sound and music-related body motion, i.e. concrete sonic, kinematic, and proprioceptive features, and on the other hand, more generic, amodal, and abstract elements in musical discourse, manifest in various symbolic representations such as notation, numbers, and diagrams. Given easily accessible music technologies, it is actually possible to experiment with different editions of musical works, i.e. concatenate fragments in different order and then evaluate the emergent contextual effects in listening experiments. Also, given the faculties of musical imagery (defined as our ability to mentally re-experience musical sound and body motion in the absence of physically present sound and body motion), we can at will recombine chunks of music in our minds and mentally scan through large musical works. The contention here is that such recombination in actual re-editing of musical sound or in musical imagery, will still be related to the basic ecological constraints of the timescales, production and perception in music.